The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0100-41582003000500013
|View full text |Cite
|
Sign up to set email alerts
|

Reação de cultivares de soja à podridão vermelha da raiz causada por Fusarium solani f. sp. glycines

Abstract: A podridão vermelha da raiz, causada por Fusarium solani f. sp. glycines, é considerada uma das doenças mais severas de soja (Glycine max) no Sul do Brasil. Este trabalho avaliou a reação de 30 genótipos de soja em experimentos conduzidos em câmara de crescimento, na Embrapa Trigo, Passo Fundo, RS. Inoculou-se o fungo nos genótipos pelo método "palito-de-dente", através da introdução de uma ponta de palito colonizada pelo fungo no hipocótilo de cada plântula e pelo método "grão de sorgo", em que o inóculo, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
1
3
0
4
Order By: Relevance
“…However, these strains can also act as pathogenic fungi (Sobowale et al, 2005), triggering Fusarium wilt, or fusariosis, which is characterized by xylem hypertrophy (Pinto et al, 2010) and wilting followed by death of the affected plants (Costa et al, 2010). The high pathogenicity of Fusarium strains in some plants of agronomic interest (Gásperi et al, 2003;Nascimento et al, 2014), together with the great economic losses triggered by fungi of this type in stored fruits (Dantas et al, 2003) or grains Ramos et al, 2014), has limited the number of studies attempting to use Fusarium strains as species that promote plant growth. Based on the absence of symptoms caused by infestation with pathogenic Fusarium strains as well as the growth response observed in the plants evaluated in this study, it can be concluded that the tested Fusarium strain is, in accordance with strict criteria, a plant growth-promoting endophytic strain.…”
Section: Discussionmentioning
confidence: 99%
“…However, these strains can also act as pathogenic fungi (Sobowale et al, 2005), triggering Fusarium wilt, or fusariosis, which is characterized by xylem hypertrophy (Pinto et al, 2010) and wilting followed by death of the affected plants (Costa et al, 2010). The high pathogenicity of Fusarium strains in some plants of agronomic interest (Gásperi et al, 2003;Nascimento et al, 2014), together with the great economic losses triggered by fungi of this type in stored fruits (Dantas et al, 2003) or grains Ramos et al, 2014), has limited the number of studies attempting to use Fusarium strains as species that promote plant growth. Based on the absence of symptoms caused by infestation with pathogenic Fusarium strains as well as the growth response observed in the plants evaluated in this study, it can be concluded that the tested Fusarium strain is, in accordance with strict criteria, a plant growth-promoting endophytic strain.…”
Section: Discussionmentioning
confidence: 99%
“…A inoculação pelo método de grãos de sorgo, em plântulas de soja, visa ndo a ca ra cteriza çã o de rea çã o de cu ltiva res de soja à F. tucumaniae, em casa de vegetação -outono/inverno 2006, resultou em infecçã o da s pla nta s, e os sintoma s típicos da doença fora m observa dos, tendo FT-Estrela alca nça do a ma ior porcenta gem de plantas mortas (90,25%). Segundo Gásperi et al (10), tanto o método "palito-de-dente" quanto o método "grão de sorgo" foram eficientes para reproduzir a doença nas plantas inoculadas.…”
Section: Análise S De C O R R E Laç ãOunclassified
“…Solos bem drenados (Silva et al, 2002), juntamente com o uso de cultivares resistentes, têm sido as práticas agronômicas mais eficientes para reduzir o impacto dessa doença (Farias Neto et al, 2006;Embrapa Soja, 2002). No entanto, a resistência à doença é parcial, tendo em vista que mesmo os genótipos considerados resistentes apresentaram sintomas típicos da podridão vermelha da raiz (Yorinori, 2000;Silva et al, 2002;Gásperi et al, 2003).…”
Section: Introductionunclassified